2018
DOI: 10.1177/1521025117751071
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Relationship Between University Students’ Psychological Flexibility and College Self-Efficacy

Abstract: For many, college is a period of transition, marked with acute stress, threats to success, and decreases in self-efficacy. For certain groups of students, the risk of these poor outcomes is elevated. In this study, 348 students from a large residential university in the western United States were surveyed to understand the role of psychological flexibility and inflexibility on self-efficacy and the potential moderating impact of year in college and underrepresented racial minority (URM) status. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 50 publications
2
18
0
5
Order By: Relevance
“…A recent study by Jeffords et al (2018), showed that psychological flexibility is closely related to self-efficacy. Self-efficacy has often been studied previously, focusing on procrastination with results showing an inverse relationship with procrastination (Howell and Watson, 2007;Steel, 2007;Wolters, 2003).…”
Section: Psychological Flexibility and Academic Self-efficacy Beliefsmentioning
confidence: 99%
“…A recent study by Jeffords et al (2018), showed that psychological flexibility is closely related to self-efficacy. Self-efficacy has often been studied previously, focusing on procrastination with results showing an inverse relationship with procrastination (Howell and Watson, 2007;Steel, 2007;Wolters, 2003).…”
Section: Psychological Flexibility and Academic Self-efficacy Beliefsmentioning
confidence: 99%
“…To sum up, our course aims to foster students' well-being by enhancing their psychological flexibility as well as their study-skills during the intervention. Recently brief social-psychological interventions have been called for, as mechanisms to improve academic performance [51]. Our intervention tool is a good example of a holistic approach to support studying at the university.…”
Section: Resultsmentioning
confidence: 99%
“…Poor well-being of university students is a common concern worldwide, and effective tools and practices to increase students' well-being are needed. We designed the intervention course to equip students with tools to enhance their well-being and also to help them to develop their study skills, because well-being should be also taken into account when fostering students learning and studying [11,51,82]. This course was based on the idea of fostering psychological flexibility, which has convincingly been shown to be an essential factor in improving psychological, social and emotional as well as physical wellbeing in many ways [38,45,82].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The range of research in 2015-2018 regarding psychological flexibility is presented as follows, Wei, et al (2015) research that explores psychological awareness and flexibility of counselors who take part in training with selfefficacy counseling, the results of the study show a positive relationship between psychological flexibility and self-efficacy. Another study on psychological flexibility and self-efficacy was also carried out by Jeffords, et al (2018) whose results were students who had high psychological flexibility, had high self-efficacy. While students who have low flexibility also have low self-efficacy as well.…”
Section: Resultsmentioning
confidence: 99%